Trends in child marriage, sexual violence, early sexual intercourse and the challenges for policy interventions to meet the sustainable development goals - Kathya Lorena Cordova-Pozo; Sujata Santosh Anishettar; Manish Kumar; Praveen Kailash Chokhandre (International Journal for Equity in Health, 2023)
Abstract Introduction Child marriage remains a prevalent issue in low- and middle-income countries (LMIC) despite global declines. Girls are disproportionately affected, facing health risks, limited education, and restricted decision-making power. We aim to provide insights for child marriage prevalence across LMIC from 1990 to 2020, with a focus on sexual violence and early sexual intercourse for public health policy interventions. Methods This study used World Bank datasets to assess progress in addressing child marriage in LMIC countries. Statistical analyses, including trend analysis and compound annual growth rate (CAGR), were conducted to evaluate indicators of first marriage, sexual violence, and sexual intercourse. Countries with sufficient data were categorized based on prevalence rates and trends, and detailed analysis focused on significant indicators. Results While significant reductions were observed in the prevalence of child marriage before the age of 15 and 18 and early sexual intercourse in most countries, few countries show increasing trends, and others could not demonstrate statistical trends due to data limitations, such as scarcity of data for boys. Overall, many countries showed a decline in sexual violence and early sexual intercourse before the age of 15, but some exhibited increasing trends. For instance, Zambia and Senegal showed a decreasing trend of sexual violence, while Nigeria exhibited an increasing trend. Notably, Uganda, Cameroon, and Sierra Leone for women, and Namibia, Zambia, and Kenya for men, experienced substantial decline in early sexual intercourse. Conclusion There is a decline in child marriage, sexual violence, and early sexual intercourse in most countries independent from the income group. Only a few countries show slight increasing trends. The improvements confirm that policies that address education, employment, and deep-rooted gender inequality at the societal level seem to be effective and help reach the SDG. However, better data are needed to enhance the understanding of the development of child marriage in these countries to improve the effectiveness of policy intervention. Therefore, we recommend that policymakers not only include existing evidence that continues progress but also increase and improve the monitoring of relevant indicators.